(untitled) (Olhares, 2019)
The article presents a debate about the important production of Roda viva in 1968 directed by Zé Celso Martinez Corrêa. The spectacle is inescapable to understand the explosive force of that year in Brazil. Despite this, it is a production in which contradictory efforts revived and aggravated in the resumption of the play 50 years later, in 2018.